Cerium oxide loaded mesoporous carbon sphere material as well as preparation method and application thereof
By efficiently dispersing the supported cerium oxide nanoparticles on mesoporous carbon spheres, the problems of poor dispersion and high cost of cerium oxide nanomaterials are solved, and higher catalytic activity and antibacterial and antifouling properties are achieved, while reducing the cost of use.
Patent Information
- Application Number
- CN202411619361.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-28
AI Technical Summary
Ceria nanomaterials have problems of poor dispersion and high cost in catalytic and materials science applications.
Mesoporous carbon spheres are used as substrates, and the cerium salt and alkaline mesoporous carbon sphere solution are acted through hydrothermal reaction to prepare a cerium oxide-supported mesoporous carbon sphere material. This method allows CeO2 nanoparticles to be highly dispersed and loaded on mesoporous carbon spheres to avoid agglomeration and enhance catalytic performance.
The antibacterial and anti-fouling performance of cerium oxide nanoparticles is improved, its catalytic activity is enhanced, the consumption of CeO2 nanoparticles is reduced, and the cost of use is reduced.
Smart Images

Figure CN119701922A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of cerium oxide composite materials, and in particular to a cerium oxide-loaded mesoporous carbon sphere material and a preparation method and application thereof. Background Art
[0002] Marine biofouling has seriously restricted the development of ships and marine engineering. The construction of green antifouling coatings is an important means of marine antifouling. Haloperoxidase is a type of natural antifouling agent secreted by marine algae, which can effectively inhibit the attachment of fouling organisms and achieve green antifouling. Natural haloperoxidase is difficult to extract and unstable, which limits its application, so people have been looking for its substitute. Nanoparticles, as an emerging material with catalytic activity similar to that of natural enzymes, are increasingly attracting attention. Inspired by the regulatable activity of natural enzymes, researchers hope to find ways to effectively regulate the activity of nanomimetic enzymes in order to obtain nanomimetic enzymes with higher catalytic efficiency. Due to its unique redox properties, the regulation of the activity of cerium dioxide (CeO2) nanomaterials is one of the research hotspots in the field of nanozymes.
[0003] Cerium oxide nanomaterials have broad prospects in many catalytic and material science applications, but they also have some disadvantages: (1) The size and dispersibility of cerium oxide particles have a significant impact on their catalytic performance. Larger cerium oxide particles may lead to reduced reaction activity, while the uneven dispersion of small-sized cerium oxide particles will affect the contact efficiency of the reactants. (2) The cost is relatively high. The cost of high-purity cerium oxide nanomaterials is relatively high, which may become a limiting factor in industrial applications. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a cerium oxide-loaded mesoporous carbon sphere material and a preparation method and application thereof, aiming to solve the technical problems of poor dispersibility of small-particle cerium oxide and high cost of cerium oxide nanomaterials.
[0005] In a first aspect, the present invention provides a method for preparing a cerium oxide-supported mesoporous carbon sphere material, comprising the following steps: S1, subjecting the cerium salt to a hydrothermal reaction in an alkaline mesoporous carbon sphere aqueous solution to obtain a mixed solution; The mass fraction of the mesoporous carbon spheres in the mixed solution is 1-4 wt %, and the concentration of the cerium salt is 0.04-0.06 mol / L; S2. The obtained mixed solution is centrifuged and washed, and vacuum dried to obtain the cerium oxide-loaded mesoporous carbon sphere material.
[0006] In the technical solution of the embodiment of the present application, mesoporous carbon spheres (MCMPs) are used as the substrate. The mesoporous carbon spheres have a large specific surface area and a uniform pore structure. CeO2 nanoparticles can be loaded on the mesoporous carbon spheres in a highly dispersed form, avoiding the agglomeration of CeO2 nanoparticles. This dispersion ensures that each CeO2 nanoparticle can fully participate in the catalytic reaction, which can expose more binding sites for CeO2 nanoparticles, provide better electron transfer conditions for CeO2 nanoparticles to simulate natural halogenated peroxidase, promote subsequent redox reactions, and enhance the antibacterial and antifouling properties of cerium oxide nanoparticles. Mesoporous carbon spheres can enhance the activity of CeO2 simulated halogenated peroxidase enzymes while reducing the consumption of CeO2 nanoparticles.
[0007] Preferably, the diameter of the mesoporous carbon sphere is about 180-220 nm and the specific surface area is 3000-2500 m 2 / g, the mesopore diameter is about 1.5~2.5 nm, and the pore volume ranges from 1.5~1.8 cm 3 / g.
[0008] Preferably, the temperature of the hydrothermal reaction is 95 to 105° C., and the reaction time is 22 to 26 h.
[0009] Preferably, the mesoporous carbon sphere aqueous solution is obtained by mixing the mesoporous carbon spheres with deionized water and subjecting the mixture to ultrasonic vibration for 1 to 2 hours.
[0010] Preferably, the cerium salt includes one or more of cerium nitrate hexahydrate, cerium chloride, cerium acetate and cerium sulfate. Preferably, the OH in the mixed solution - The concentration is 0.8~1.2 mol / L.
[0011] Preferably, the OH in the mixed solution - The source includes either sodium hydroxide or potassium hydroxide or both Preferably, the vacuum freeze-drying conditions in step S2 are a temperature of -80 to -60°C and a drying time of 22 to 26 hours.
[0012] In a second aspect, an embodiment of the present application provides a cerium oxide-loaded mesoporous carbon sphere material prepared by the above method.
[0013] In a third aspect, an embodiment of the present application provides a coating antifouling agent, comprising a mesoporous carbon sphere material supported by cerium oxide.
[0014] Different from the existing technical solutions, the beneficial effects of this application include: The present application adopts mesoporous carbon spheres as substrates. The mesoporous carbon spheres have a large specific surface area and a uniform pore structure. The pore structure of the mesoporous carbon spheres is very close to the diameter of the short rod-type CeO2. This size matching enables the short rod-type CeO2 to be embedded in the pores of the mesoporous carbon spheres to form a close physical contact. At the same time, the hydroxyl groups on the surface of the carbon spheres can form stable covalent bonds with the oxygen vacancies on the surface of the CeO2 particles, thereby improving the binding strength and service life of the mesoporous carbon spheres loaded with cerium oxide; CeO2 nanoparticles can be loaded on the mesoporous carbon spheres in a highly dispersed form, thereby avoiding the agglomeration of CeO2 nanoparticles. This dispersion ensures that each CeO2 nanoparticle can fully participate in the catalytic reaction, and can expose more binding sites for the CeO2 nanoparticles, thereby providing better electron transfer conditions for the CeO2 nanoparticles to simulate natural halogenated catalase, promoting subsequent redox reactions, and enhancing the antibacterial and antifouling properties of the cerium oxide nanoparticles. Mesoporous carbon spheres can enhance the activity of CeO2 haloperoxidase-simulated enzymes while reducing the consumption of CeO2 nanoparticles, thereby reducing the cost of use.
[0015] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 a-1, a-2, and a-3 are TEM morphology images of MCMPs-CeO2 in Examples 1 to 3, respectively. Figure 1 b-1, b-2, and b-3 are HR-TEM morphology images of MCMPs-CeO2 in Examples 1 to 3, respectively.
[0018] Figure 2 a-1, a-2, and a-3 are the TEM morphologies of GO-CeO2 in Comparative Examples 1 to 3, respectively. Figure 2 b-1, b-2, and b-3 are the HR-TEM morphology images of GO-CeO2 in comparative examples 1 to 3, respectively.
[0019] Figure 3 It is the change value of phenol red in the UV-visible spectrum of MCMPs-CeO2 in Examples 1 to 3 over time after gravity sedimentation.
[0020] Figure 4 The values of phenol red in the UV-visible spectra of GO-CeO2 in Comparative Examples 1 to 3 change with time after gravity sedimentation.
[0021] Figure 5 It is the cfu after the antibacterial performance test of the blank control group (Control), commercially available CeO2 (Commercially available CeO2) and the MCMPs-CeO2 prepared in Examples 1 to 3.
[0022] Figure 6 It is the antibacterial rate after the antibacterial performance test of the blank control group (Control), commercially available CeO2 (Commercially available CeO2) and the MCMPs-CeO2 prepared in Examples 1 to 3. DETAILED DESCRIPTION
[0023] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0025] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0026] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0027] Cerium oxide nanomaterials have broad prospects in many catalytic and material science applications, but they also have some disadvantages: (1) The size and dispersibility of cerium oxide particles have a significant impact on their catalytic performance. Larger cerium oxide particles may lead to reduced reaction activity, while the uneven dispersion of small-sized cerium oxide particles will affect the contact efficiency of the reactants. (2) The cost is relatively high. The cost of high-purity cerium oxide nanomaterials is relatively high, which may become a limiting factor in industrial applications.
[0028] In order to solve the technical problems of poor dispersibility of small-particle cerium oxide and high cost of cerium oxide nanomaterials, the present application provides a cerium oxide-loaded mesoporous carbon sphere material and its preparation method and application, wherein, by using mesoporous carbon spheres as a substrate, the mesoporous carbon spheres have a large specific surface area and a uniform pore structure, and the pore structure of the mesoporous carbon spheres is very close to the diameter of short rod-type CeO2. This size matching enables the short rod-type CeO2 to be embedded in the pores of the mesoporous carbon spheres to form a close physical contact; CeO2 nanoparticles can be loaded on the mesoporous carbon spheres in a highly dispersed form, avoiding the agglomeration of CeO2 nanoparticles. This dispersion ensures that each CeO2 nanoparticle can fully participate in the catalytic reaction, and can expose more binding sites for the CeO2 nanoparticles, providing better electron transfer conditions for the CeO2 nanoparticles to simulate natural halogenated peroxidase, promoting subsequent redox reactions, and enhancing the antibacterial and antifouling properties of the cerium oxide nanoparticles. Mesoporous carbon spheres can enhance the activity of CeO2 simulated haloperoxidase while reducing the consumption of CeO2 nanoparticles.
[0029] In a first aspect, the present invention provides a method for preparing a cerium oxide-supported mesoporous carbon sphere material, comprising the following steps: S1, subjecting the cerium salt to a hydrothermal reaction in an alkaline mesoporous carbon sphere aqueous solution to obtain a mixed solution; The mass fraction of the mesoporous carbon spheres in the mixed solution is 1-4 wt %, and the concentration of the cerium salt is 0.04-0.06 mol / L; S2. The obtained mixed solution is centrifuged and washed, and vacuum dried and purified to obtain the cerium oxide-loaded mesoporous carbon sphere material.
[0030] Preferably, the diameter of the mesoporous carbon sphere is about 180-220 nm and the specific surface area is 3000-2500 m 2 / g, the mesopore diameter is about 1.5~2.5 nm, and the pore volume ranges from 1.5~1.8 cm 3 / g.
[0031] Preferably, the temperature of the hydrothermal reaction is 95 to 105° C., and the reaction time is 22 to 26 h.
[0032] Preferably, the mesoporous carbon sphere aqueous solution is obtained by mixing the mesoporous carbon spheres with deionized water and subjecting the mixture to ultrasonic vibration for 1 to 2 hours.
[0033] Preferably, one or more of cerium nitrate hexahydrate, cerium chloride, cerium acetate and cerium sulfate.
[0034] Preferably, the OH in the mixed solution - The concentration is 0.8~1.2 mol / L.
[0035] Preferably, the OH in the mixed solution - The source includes one or both of sodium hydroxide and potassium hydroxide.
[0036] Preferably, the vacuum freeze-drying conditions in step S2 are a temperature of -80 to -60°C and a drying time of 22 to 26 hours.
[0037] In the technical solution of the embodiment of the present application, when a hydrothermal reaction is carried out in an alkaline mesoporous carbon ball solution, CeO2 on MCMPs-CeO2 originates from Ce 3+ and OH - The unstable precursor Ce(OH)3 combined with NaOH during the preparation process increases the concentration of OH- ions. 3+ Ions are more easily converted into Ce 4+ Ion, Ce 4+ The ions prefer to combine with OH- ions. In this case, the CeO2 nucleus undergoes Ostwald ripening, which promotes the dissolution and recrystallization of the CeO2 nucleus, inducing competitive growth of CeO2 crystals, causing some CeO2 crystals to break through the growth restrictions of mesoporous carbon spheres and develop into short rods. As the amount of mesoporous carbon spheres increases, the ability of CeO2 crystals to break through the load restrictions of mesoporous carbon spheres becomes stronger, and the morphology of some CeO2 crystals in the initial MCMPs-CeO2 transitions from quantum dots to short rods. The diameters of mesoporous carbon spheres and short rod CeO2 are very close, and this size match allows short rod CeO2 to be embedded in the pores of mesoporous carbon spheres to form close physical contact.
[0038] In a second aspect, an embodiment of the present application provides a cerium oxide-loaded mesoporous carbon sphere material prepared by the above method.
[0039] In a third aspect, an embodiment of the present application provides a coating antifouling agent, comprising a mesoporous carbon sphere material supported by cerium oxide.
[0040] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0041] 1. Preparation method Example 1 A method for preparing a cerium oxide-loaded mesoporous carbon sphere material comprises the following steps: 3.75 mg of mesoporous carbon spheres were weighed and poured into 35 mL of deionized water, and ultrasonically vibrated for 1 h. 868 mg of Ce(NO3)3·6H2O was weighed and dissolved in 5 mL of deionized water and placed in a centrifuge tube. After the ultrasonic treatment, the dissolved Ce(NO3)3·6H2O and 1600 mg of NaOH were successively poured into the mesoporous carbon sphere solution and stirred at room temperature for 30 min. The solution was then transferred to a high-temperature reactor (100 ℃, 24 h). Finally, the final sample was obtained by centrifugation and vacuum drying (60 ℃, 24 h). Theoretical calculations show that the mass fraction of mesoporous carbon spheres is about 1%, named 1wt% MCMPs-CeO2.
[0042] The mesoporous carbon spheres used in this example were purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0043] The cerium nitrate hexahydrate used in this example was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a purity of 99.5%.
[0044] The sodium hydroxide used in this embodiment was purchased from Sinopharm Chemical Reagent Co., Ltd. with a purity of 96%.
[0045] Example 2 The difference between Example 2 and Example 1 is that 7.5 mg of mesoporous carbon spheres are added to 35 mL of deionized water, and the remaining steps are consistent with Example 1. The mass fraction of mesoporous carbon spheres is about 2%, named 2wt% MCMPs-CeO2.
[0046] Example 3 The difference between Example 3 and Example 1 is that 15 mg of mesoporous carbon spheres are added to 35 mL of deionized water, and the remaining steps are consistent with Example 1. The mass fraction of mesoporous carbon spheres is about 4%, named 4wt% MCMPs-CeO2.
[0047] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that 3.75 mg of graphene oxide (GO) is added to 35 mL of deionized water, and the remaining steps are consistent with Example 1. The mass fraction of graphene oxide is about 1%, named 1wt% MCMPs-CeO2.
[0048] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that 7.5 mg of graphene oxide (GO) is added to 35 mL of deionized water, and the remaining steps are consistent with Example 1. The mass fraction of graphene oxide is about 2%, named 2wt% MCMPs-CeO2.
[0049] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that 15 mg of graphene oxide (GO) is added to 35 mL of deionized water, and the remaining steps are consistent with Example 1. The mass fraction of graphene oxide is about 4%, named 4wt% MCMPs-CeO2.
[0050] 2. Test Method 1. TEM and HR-TEM scanning methods: Prepare a suspension of the sample to be tested, dilute it to a transparent state, and oscillate the suspension until it is uniform. Use a pipette to drop a small amount of the suspension onto a copper sheet and air-dry it. Use TEM and HR-TEM to scan it, respectively, to obtain TEM morphology images and HR-TEM morphology images.
[0051] 2. Antibacterial performance analysis method: The concentration of Escherichia coli in 0.9 wt % NaCl solution is 10 6 cells / mL. Set up 6 groups as follows: Control group: control, E. coli suspension + 25 mmol / L NH4Br + 0.1 mol / L H2O2; 4 experimental groups: E. coli suspension + 25 mmol / L NH4Br + 0.1 mol / L H2O2 + 5 × 10 - 4 mol / L of 4 different powders (commercial CeO2, 1 wt % MCMPs-CeO2, 2 wt % MCMPs-CeO2, 4 wt % MCMPs-CeO2).
[0052] Each group was incubated at 37°C in a pre-sterilized 24-well plate. After 4 h of incubation, the bacterial suspension was serially diluted with sterile 0.9 wt % NaCl solution, and 100 μL of the dilution was evenly distributed on the nutrient agar plate. After 24 h of incubation at 37°C, a photo of each agar plate was taken for antibacterial analysis. The bacterial colony forming units on the agar plates were counted using ImageJ software to quantitatively analyze the antibacterial efficiency.
[0053] 3. Test method for the change of phenol red over time in UV-visible spectrum MCMPs-CeO2 and GO-CeO2 mimic natural haloperoxidase in the presence of bromine source (NH4Br) and H2O2 to bromine phenol red to bromophenol blue. The bromination reaction was carried out at room temperature. A 3 mL solution containing 5 × 10 -4 mol / L sample powder, 50 μmol / L phenol red solution, 25 mmol / L NH4Br solution and 1 mmol / L H2O2. The absorption spectrum scan at 432 nm was recorded with a visible spectrophotometer (722G) at a fixed time interval of 10 minutes.
[0054] III. Analysis of test results of various embodiments and comparative examples (1) TEM scanning was performed on the MCMPs-CeO2 prepared in Examples 1 to 3 to obtain a TEM morphology image, as shown in FIG. Figure 1 As shown, Figure 1 a-1, a-2, and a-3 are the TEM morphologies of MCMPs-CeO2 in Examples 1 to 3, respectively. Figure 1 b-1, b-2, and b-3 are the morphology images of MCMPs-CeO2 HR-TEM in Examples 1 to 3, respectively.
[0055] from Figure 1 It can be seen from a-1 that the amount of MCMPs added is 1wt%, which is a small amount. MCMPs-CeO2 has a three-dimensional spherical structure. Figure 1 a-1 to Figure 1 a-3, as the amount of MCMPs added gradually increased, part of the CeO2 on the MCMPs-CeO2 underwent a morphological change, and the aggregation of CeO2 was inhibited. 3+ and OH - The unstable precursor Ce(OH)3 is combined. The NaOH added during the preparation process causes OH - As the ion concentration increases, Ce 3+ Ions are more easily converted into Ce 4+ Ion, Ce 4+Ions prefer to combine with OH- ions. In this case, the CeO2 nucleus undergoes Ostwald ripening, which promotes the dissolution and recrystallization of the CeO2 nucleus, induces the competitive growth of CeO2 crystals, and causes some CeO2 crystals to break through the growth restriction of mesoporous carbon spheres and develop into short rods. As the amount of mesoporous carbon spheres increases, the CeO2 crystals have a stronger ability to break through the loading restriction of mesoporous carbon spheres. The initial MCMPs-CeO2 crystal morphology changes from quantum dots (see Figure 1 b-1) Transition to short stick type (see Figure 1 b-3).
[0056] The lattice fringe spacings in MCMPs-CeO2 are 3.12 and 2.71 Å, corresponding to the (111) and (200) planes of CeO2, respectively (see Figure 1 ch). Therefore, from Figure 1 Image analysis showed that CeO2 had been successfully loaded into the mesoporous carbon spheres, and part of the CeO2 morphology was transformed into rod-type.
[0057] The GO-CeO2 prepared in Examples 1 to 3 was subjected to TEM and HR-TEM scanning to obtain TEM and HR-TEM morphology images, as shown in FIG. Figure 2 As shown, Figure 2 a-1, a-2, and a-3 are the TEM morphologies of GO-CeO2 in Comparative Examples 1 to 3, respectively. Figure 2 b-1, b-2, and b-3 are the HR-TEM morphology images of GO-CeO2 in comparative examples 1 to 3, respectively.
[0058] Depend on Figure 2 It can be seen that 1wt% GO-CeO2 ( Figure 2 a-1) CeO2 is long rod (few) + short rod (many) type; 2wt% GO-CeO2 ( Figure 2 a-2) CeO2 is short rod type; 4wt% GO-CeO2 ( Figure 2 In a-3 & b-3), CeO2 is of the long rod (many) + short rod (few) type.
[0059] Comparing the growth of CeO2 crystals loaded on MCMPs and GO with different dosages, it can be seen that the spatial utilization of CeO2 in the 4wt% MCMPs-CeO2 group is higher than that in the 4wt% GO-CeO2 group, because the diameters of the mesoporous carbon spheres and the short-rod CeO2 are very close, and this size matching enables the short-rod CeO2 to be embedded in the pores of the mesoporous carbon spheres, forming a close physical contact, and at the same time, the short-rod CeO2 is dispersed in the pores of the mesoporous carbon spheres, with strong dispersion and will not interfere with the growth of other CeO2. In the 4wt% GO group, most of the CeO2 crystal nuclei are quickly formed into long rods, and some of the long rods hinder the growth of other CeO2, forming a short rod structure, resulting in a sparse layout of CeO2 on the GO loading layer and the generation of gaps, reducing the spatial utilization of GO.
[0060] (2) MCMPs-CeO2 and GO-CeO2 mimic natural haloperoxidase in the presence of bromine source (NH4Br) and H2O2, brominating phenol red to bromophenol blue. Figure 3 Schematic diagram of the change in OD value of phenol red consumption detected by UV-Vis of MCMPs-CeO2 in Examples 1 to 3 at a wavelength of 432 nm 110 min ago. Figure 4 Schematic diagram of the change in OD value of phenol red consumption detected by UV-Vis of MCMPs-CeO2 in comparative examples 1 to 3 at a wavelength of 432 nm 100 min ago.
[0061] The slope of the MCMPs-CeO2 composite materials in Examples 1 to 3 before 110 min is named K 1wt% MCMPs−CeO2 , K 2wt% MCMPs−CeO2 , K 4wt% MCMPs−CeO2 ; The slope and speed of GO-CeO2 in Comparative Examples 1 to 3 before 100 min are named K 1wt% GO−CeO2 , K 2wt% GO−CeO2 , K 4wt% GO−CeO2 The slope K represents the changing trend of the OD value per unit time. The larger the absolute value of K, the greater the activity of the haloperoxidase.
[0062] from Figure 3 It can be concluded that K 4wt% MCMPs−CeO2 = -6.08 × 10 -3 , K 2wt% MCMPs−CeO2 = -4.73 × 10 -3 , K 1wt% MCMPs−CeO2 = -2.73 × 10 -3 This indicates that 4wt% MCMPs-CeO2 has the highest rate of consuming phenol red, the highest haloperoxidase activity, and the best antibacterial and antifouling properties. Figure 4It can be concluded that among the three GO-CeO2 in Comparative Examples 1 to 3, 4wt% GO-CeO2 has the highest haloperoxidase activity, slightly higher than 2wt% GO-CeO2. Both of them may have strong haloperoxidase activity. 3+ defects, under the amplification effect of GO's electron transfer ability, 2wt% GO-CeO2 has the best antibacterial and antifouling properties. 4wt% MCMPs−CeO2 = -6.08 × 10 -3 , K 2wt% GO−CeO2 = -5.38 × 10 -3 , indicating that the antibacterial performance of 4wt% MCMPs-CeO2 is better than that of 2wt% GO-CeO2. Figure 1 and Figure 2 It can be concluded that MCMPs-CeO2 can provide a larger surface area for CeO2.
[0063] (3) The antibacterial properties of the blank control group (Control), commercially available CeO2, MCMPs and MCMPs-CeO2 prepared in Examples 1 to 3 were analyzed. The number of bacteria was shown in Figure 5 , antibacterial rate Figure 6 .
[0064] from Figure 5 As can be seen from the figure, the average bacterial numbers of the control, commercially available CeO2 group, MCMPs group, 1wt% MCMPs-CeO2 group, 2wt% MCMPs-CeO2 group, and 4wt% MCMPs-CeO2 group were 9.7×10 4 , 1.3×10 4 ,7.75×10 4 ,7.35×10 4 and 6×10 3 Taking the blank group data as the benchmark, the bacterial inhibition rates of the commercial CeO2 group, 1wt% MCMPs-CeO2 group, 2wt% MCMPs-CeO2 group and 4wt% MCMPs-CeO2 group ( Figure 6), are 86.60%, 20.10%, 24.23% and 93.44% respectively. The results show that different amounts of mesoporous carbon spheres of MCMPs-CeO2 have different antibacterial properties in marine environment. The antibacterial effect of 4wt% MCMPs-CeO2 is the best, reaching 93.44%. The antibacterial rates of 1wt% MCMPs-CeO2 group and 2wt% MCMPs-CeO2 group are relatively low. Under this condition, cerium oxide agglomerates on mesoporous carbon, which is equivalent to agglomerating into micron-level balls. In fact, the exposed cerium oxide is only cerium oxide on the surface of microspheres, and the exposure degree of cerium oxide active sites is low, which leads to a decrease in antibacterial activity; with the increase of the proportion of mesoporous carbon spheres, CeO2 crystals break through the limitation of mesoporous carbon sphere growth and develop into short rods. The exposure degree of CeO2 active sites increases, so that its antibacterial properties are fully exerted. Therefore, the antibacterial rate of 4wt% MCMPs-CeO2 group is greatly improved. The CeO2 content in 4wt% MCMPs-CeO2 is much lower than that in the commercial CeO2 group, indicating that mesoporous carbon spheres can enhance the activity of CeO2 simulating haloperoxidase while reducing the consumption of CeO2 nanoparticles.
[0065] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a cerium oxide-supported mesoporous carbon sphere material, characterized in that: The steps include: S1, subjecting the cerium salt to a hydrothermal reaction in an alkaline mesoporous carbon sphere aqueous solution to obtain a mixed solution; The mass fraction of the mesoporous carbon spheres in the mixed solution is 1-4wt%, and the concentration of the cerium salt is 0.04-0.06mol / L; S2. The obtained mixed solution is centrifuged and washed, and vacuum dried to obtain the cerium oxide-loaded mesoporous carbon sphere material.
2. The method for preparing the cerium oxide-supported mesoporous carbon sphere material according to claim 1, characterized in that: The mesoporous carbon sphere has a diameter of 180-220 nm and a specific surface area of 3000-2500 m 2 / g, the mesopore diameter is 1.5~2.5 nm, and the pore volume ranges from 1.5~1.8 cm 3 / g.
3. The method for preparing the cerium oxide-supported mesoporous carbon sphere material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 95-105° C., and the reaction time is 22-26 h.
4. The method for preparing the cerium oxide-supported mesoporous carbon sphere material according to claim 1, characterized in that: The mesoporous carbon sphere aqueous solution is obtained by mixing the mesoporous carbon spheres with deionized water and subjecting the mixture to ultrasonic vibration for 1 to 2 hours.
5. The method for preparing the cerium oxide-supported mesoporous carbon sphere material according to claim 1, characterized in that: The cerium salt includes one or more of cerium nitrate hexahydrate, cerium chloride, cerium acetate and cerium sulfate.
6. The method for preparing the cerium oxide-supported mesoporous carbon sphere material according to claim 1, characterized in that: The OH in the mixed solution - The concentration is 0.8~1.2 mol / L.
7. The method for preparing the cerium oxide-supported mesoporous carbon sphere material according to claim 1, characterized in that: The OH in the mixed solution - The source includes one or both of sodium hydroxide and potassium hydroxide.
8. The method for preparing the cerium oxide-supported mesoporous carbon sphere material according to claim 1, characterized in that: The vacuum freeze-drying conditions in step S2 are a temperature of -80 to -60°C and a drying time of 22 to 26 hours.
9. A cerium oxide-supported mesoporous carbon sphere material, characterized in that: The cerium oxide-supported mesoporous carbon sphere material is prepared by the method for preparing the cerium oxide-supported mesoporous carbon sphere material according to any one of claims 1 to 8.
10. A coating antifouling agent, characterized in that: The invention comprises the cerium oxide-supported mesoporous carbon sphere material as claimed in claim 9.
Citation Information
Patent Citations
Metallic oxide / carbon fiber composite material and preparation method and applications thereof
CN101662029A
Mesoporous cerium dioxide hollow spheres or mesoporous cerium dioxide / carbon composite material hollow spheres and preparation method thereof
CN106622206A
Platinum-based catalyst for hydrogen fuel cell as well as preparation method and application of platinum-based catalyst
CN116487620A
Mesoporous cerium oxide nano material as well as preparation method and application thereof
CN117416985A
Cited By
Active and passive synergistic antifouling coating with low surface energy and preparation method thereof
CN121914598A
A low surface energy active-passive synergistic antifouling coating and its preparation method
CN121914598B